Increasing Sales for Kalitengah Village SMEs Through Effective Digital Marketing Seminars: Meningkatkan Penjualan UMKM Desa Kalitengah Melalui Seminar Digital Marketing yang Efektif (Indonesian Journal of Cultural and Community Development, 2024)
Kuliah Kerja Nyata (KKN) is a pivotal intramural activity that integrates education with community service, aimed at fostering the Three Higher Dharma. General Background: In the context of Indonesia's economic landscape, Micro, Small, and Medium Enterprises (SMEs) are vital for local economic development but often lack effective marketing strategies. Specific Background: This study addresses the gap in digital marketing knowledge among SMEs in Kalitengah, Tanggulangin, particularly within the Muhammadiyah Branch community. Knowledge Gap: Despite the potential benefits of digital marketing, many SMEs remain unaware of its effective implementation, leading to limited economic growth. Aims: This research aims to evaluate the impact of digital marketing seminars on the growth and sustainability of local SMEs. Results: A survey of 30 SMEs participating in a seminar revealed a 90% participation rate, demonstrating high engagement. Post-seminar analysis indicated significant improvements in marketing strategies and business performance. Novelty: This study contributes new insights into the relationship between digital marketing education and SME development in rural Indonesia. Implications: The findings underscore the necessity of ongoing digital training for SMEs, suggesting that enhanced marketing capabilities can significantly improve the economic resilience of local communities, thereby supporting broader economic development objectives.Highlights: • Impact of Digital Marketing: The seminar significantly improved marketing strategies and business performance for local SMEs in Kalitengah.• High Engagement: A 90% participation rate indicates strong interest and commitment from the community towards enhancing their business skills.• Ongoing Education: The study emphasizes the necessity for continuous digital marketing training to foster economic resilience in rural areas.Keywords: Kuliah Kerja Nyata, Digital Marketing, SMEs, Community Development, Muhammadiyah.